2021
DOI: 10.1007/s44197-021-00021-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined Blood Indexes of Systemic Inflammation as a Mirror to Admission to Intensive Care Unit in COVID-19 Patients: A Multicentric Study

Abstract: Background The Coronavirus 2019 is a pandemic that has spread worldwide, threatening human health. The main cause of death in patients with COVID-19 is a systemic pro-inflammatory mechanism that quickly progresses to acute respiratory distress syndrome. Hematological ratios as affordable indicators of inflammatory response were studied in COVID-19 patients. The study aimed to study the importance of the blood cell indexes of the systemic inflammatory response, as the Aggregate Index of Systemic I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 30 publications
2
47
0
1
Order By: Relevance
“…AISI, NLPR, SII, and SIRI were associated with admission to ICU in the study by Hamad et al (22). Similar to this study, NLRP sensitivity was the highest index (cut-off >0.0195, 61.3%) (22).…”
Section: Discussionsupporting
confidence: 88%
“…AISI, NLPR, SII, and SIRI were associated with admission to ICU in the study by Hamad et al (22). Similar to this study, NLRP sensitivity was the highest index (cut-off >0.0195, 61.3%) (22).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding hematological indices, NLR and SII have been analyzed in numerous articles published recently [ 19 , 22 , 23 , 56 , 65 , 66 ]. Thus, Moisa et al [ 56 ] demonstrated that a basal value of NLR > 11 (HR:4.6; 95% CI:2.80–7.56; p < 0.001), MLR >0.64 (HR:2.38; 95% CI:1.70–3.33; p < 0.001), and SII > 3700 (HR:2.44; 95% CI:1.68–3.54; p < 0.001) are independent prognostic factors of mortality for the 272 patients diagnosed with COVID-19 [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kudlinsky et al published an article in which they proved the prognostic impact of NLR > 11.57 ( p = 0.0008) and SII > 2058 ( p = 0.02) in COVID-19 patients’ death [ 65 ]. In a cohort study involving 411 COVID-19 patients, Regolo et al discovered a correlation between baseline NLR values greater than 11.38 and the necessity for ICU admission ( p < 0.0001) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Zinellu et al (2021) underlined its prognostic significance to predict poor outcomes in idiopathic pulmonary fibrosis [ 72 ]. Furthermore, Hamad and coworkers (2021) also studied its importance in patients suffering from COVID-19 [ 23 ]. Although it was significant in univariate analysis, like SII, it did not convey a sufficient prognostic value in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous novel inflammatory markers have been described that involve the systemic inflammatory response index (SIRI—the quotient of neutrophils and monocytes, divided by lymphocyte count), the aggregate index of systemic inflammation (AISI—the quotient of neutrophils, monocytes, and platelets, divided by lymphocyte count), and the systemic inflammatory index (SII), composed of the quotient of neutrophils and platelets divided by lymphocyte counts [ 23 ]. These three indices have been presented as possible mortality prognostic factors in different cardiovascular and non-cardiovascular diseases [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%